Fine‐ and coarse‐filter conservation strategies in a time of climate change. (12th July 2014) - Tingley, Morgan W.; Darling, Emily S.; Wilcove, David S.
Abstract : As species adapt to a changing climate, so too must humans adapt to a new conservation landscape. Classical frameworks have distinguished between fine‐ and coarse‐filter conservation strategies, focusing on conserving either the species or the landscapes, respectively, that together define extant biodiversity. Adapting this framework for climate change, conservationists are using fine‐filter strategies to assess species vulnerability and prioritize the most vulnerable species for conservation actions. Coarse‐filter strategies seek to conserve either key sites as determined by natural elements unaffected by climate change, or sites with low climate velocity that are expected to be refugia for climate‐displaced species. Novel approaches combine coarse‐ and fine‐scale approaches—for example, prioritizing species within pretargeted landscapes—and accommodate the difficult reality of multiple interacting stressors. By taking a diversified approach to conservation actions and decisions, conservationists can hedge against uncertainty, take advantage of new methods and information, and tailor actions to the unique needs and limitations of places, thereby ensuring that the biodiversity show will go on.